Financial Analysis Of Information Technology Sector In India - Veeraraghavan, Dr. Ravi (Migration Letters, 2024)
This research paper analyses the financial parameters of Information Technology (IT) Companies listed in the National Stock Exchange of India as of 15th August 2023. The initial analysis relates to 240 companies but a deeper analysis has been done for 99 companies that have an annual revenue of INR 100 Crores or more. This research analyses the financial performance of the 99 companies considering their revenue growth, profitability, solvency, market performance and financial strength for the year ended 31st March 2023. Based on the revenue, the 99 companies have been classified into Very Large, Large, Medium and Small Companies. 10 financial ratios have been considered to analyse the performance of each category. Piotrowski’s F Score has been used to measure the financial strength of these companies and Altman’s Z Score to assess the financial solvency of the IT companies. This analysis reveals four important things about IT companies – (1) The Top 7 companies (“Very Large”) contribute more than 80% of the revenue as well as market capitalization, while the Bottom 141 companies (out of 240) contribute just around 0.5% of market capitalization and revenue. 28% of companies under the “small” category have sales growth below 10%. (2) All The companies under the “very large” category have a good price-earnings ratio (20 or more) (3) 34% of the companies have a profit margin of 5% or less. (4) 46% of the companies in the IT Sector have a current ratio below 2 (5) 90% of the companies in the IT Sector have a Z Score above the safe zone (6). Only 2 out of 17 companies (12%) have a Piotroski F score of 8+ in Very Large and Large categories, while 10 out of 82 companies (12%) in Small and Medium companies also have a score of 8+. The study of financial parameters also covers the relationship between the financial parameters of the 99 companies. This analysis reveals that (1) Only the relationship between Profit on Sales and Return on Capital employed (which is, moderate to strong positive) is similar for all four categories of companies in the IT Sector and (2) The correlation between fina[1]ncial parameters at Sector level is driven primarily by the small companies as the number of small companies are significantly high. The results obtained for “Very Large” Companies are mostly different from the ones obtained at the Sector Level.